Environmental parameters and abundance of mexican oregano (Lippia graveolens) in the Tamaulipas state - Haidé-Quezada, Flor (Universidad Autónoma de Tamaulipas, 2011)
Oregano is a bushy herbaceous plant, commonly used in culinary purposes. Its economic importance is due to their uses not only as a condiment for food but also in cosmetics, pharmaceuticals and liquor. The objective of this research was to study the ecological distribution, presence and abundance of populations of oregano (Lippia graveolens HBK) and contribute to current knowledge of the ecological status of this species in Tamaulipas, Mexico. In field surveys directed in Mendez, San Carlos, Hidalgo, Casas, Jaumave and Bustamante, This are Tamaulipas municipalities where is presented and distributed oregano, and the study showed that there was an average abundance of 905 plants per hectare oregano. When setting up this parameter, the more abundant quantities of oregano where founf in the municipality of Jaumave which was followed by Mendez and Hidalgo. This study shows the vegetation types in which oregano is abundant. Particularly L. graveolens are thorny bushes and scrub that is located under high Subin. The total abundance of L. graveolens was represented by 2173 individuals distributed among the 24 sampling sites. The information obtained is important to determine actions for sustainable management or conservation ecology.